The Effect of Binahong Leaves (Anredera cordifolia) Decoction on Perineal Wound Healing among Post-Partum Women - Shinta Novelia; Siti Syamsiah; Risa Aprilia (Health and Technology Journal (HTechJ), 2023)
The puerperium is a period of recovery for the uterine organs as they were before pregnancy as well as physical and psychological changes in the mother. One of the problems during the puerperium is the perineal wound that occurs due to a spontaneous wound or episiotomy during delivery. The wound can be said to be healed if within 1 week the condition of the wound is dry, closed and there are no signs of infection. Delay in the healing time of perineal wounds can be a problem including bladder and birth canal infections. This study aims to determine the effect of water decoction of binahong leaves (Anredera cordifolia) on the healing of perineal wounds among postpartum women at PMB "M" Bogor Regency in 2022. This type of research uses a quasi-experimental research design with a posttest-only research design. The population and samples in this study were postpartum mothers with perineal injuries of degrees I-II as many as 30 respondents. The sampling technique in this study was total sampling and data collection was carried out by observation. Data analysis was performed using the Mann-Whitney U test to determine the effect of intervention in one intervention group compared to the control group. The results showed that there was an effect of boiled water from binahong leaves on the healing of perineal wounds with first- and second-degree wounds in postpartum women. The results of the Mann-Whitney U test obtained a p-value of 0.000 (<0.05). The use of boiled water from binahong leaves can accelerate the healing process of perineal wounds among postpartum women at BPM "M" Bogor Regency. It is hoped that the use of boiled water from binahong leaves can be recommended and applied by health workers to postpartum women who experience grades I and II perineal injuries.